UPAYA PENINGKATAN KEMAMPUAN BERPIKIR KRITIS MATEMATIKA MELALUI MODEL PEMBELAJARAN PROBLEM POSING - Sutrisno, Joko; Pratama, Elvandri Yogi (LPPM STKIP PGRI Bandar Lampung, 2020)
Abstract: The research started from the low critical thinking ability of students in mathematics lessons in class VIII D SMP Negeri 16 Bandar Lampung in the 2020/2021 school year. The purpose of this research is to improve students' mathematical critical thinking skills through the application of the Problem Posing learning model. This research is a classroom action research conducted in two cycles. The subjects in this study were students of class VIII D SMP Negeri 16 Bandar Lampung, amounting to 27 people, while the object in this study was the students' critical thinking ability in participating in mathematics learning. Data collection techniques using test and observation techniques. The data analysis technique used in this study consisted of: 1) analysis of observation results, 2) analysis of critical thinking ability test results. To check the degree of trustworthiness of the data, this study used triangulation of other research sources, namely school principals, mathematics teachers, and students. Based on the results of data analysis, it can be concluded that there is an increase in students' critical thinking skills in learning mathematics. The improvement of students' critical thinking skills in learning mathematics is as follows: in the pre-cycle who passed there were 5 people or 18.52%, and 22 people did not pass or 81.48%, increased in the first cycle, namely 9 people (33.33%) who passed and 18 people (66.67%) did not pass, and in the second cycle there were 21 people (77.78%) who passed well and 6 people (22.22%) did not pass.